Epidemiological study of skin disorders in Andaman and Nicobar Islands - Pradeep Balasubramanian; Anjali J Anil (Wolters Kluwer Medknow Publications, 2021)
Background: The study pertaining to the prevalence of diseases plays a valuable tool in the planning and implementation of health care facilities. The prevalence of skin diseases in Andaman and Nicobar islands, which is rightly called "Little India" considering the heterogeneity of the people living here, will serve as an indispensable tool. Methodology: The data from the outpatient records of the Dermatology Department of 2 consecutive years were collected retrospectively, the study duration being January 2017 to December 2018. The diagnoses were classified as per the International Classification of Diseases (ICD 10). The quantitative variables are expressed as numbers and percentages. Results: Cutaneous infections namely dermatophyte infection, tinea versicolor, impetigo, scabies, molluscum, and warts were the most commonly encountered disorders. Hansen's disease was witnessed in 42 patients. Among the tribals, scabies, dermatophytosis, and pyoderma were the commonly encountered cutaneous disorders. Conclusion: Thus, the data presented in the present study can be extrapolated on the mainland considering the diversity of the population in the Andaman and Nicobar (A and N) Islands.